2003
DOI: 10.1167/iovs.02-1301
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human β-Defensins in Conjunctival Epithelium: Relevance to Dry Eye Disease

Abstract: hBD-2 was expressed only in the conjunctival epithelium of patients with moderate dry eye. Because cytokines such as IL-1beta and TNF-alpha induced the expression of hBD-2 by conjunctival epithelial cells and because increased proinflammatory cytokine activity is a feature of dry eye disease, it can be speculated that the hBD-2 upregulation observed in subjects with moderate dry eye is mediated by proinflammatory cytokine activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 50 publications
4
55
2
1
Order By: Relevance
“…17,18 Human β-defensin-1 (hBD-1) and hBD-3 are constitutively expressed by the corneal and conjunctival epithelia, 18-20 whereas the expression of hBD-2 is inducible by proinflammatory cytokines such as IL-1α, IL-1β, TNF-α, bacterial by-products such as lipopolysaccharide and heat-killed Pseudomonas aeruginosa, and injury. [19][20][21][22] We have also observed that hBD-2 is expressed by conjunctival epithelial cells from patients with moderate dry eye but not in cells from normal subjects. 20 Because it has been reported that proinflammatory cytokines are secreted in greater amounts by HCECs in hyperosmolar media, 10 we reasoned that a differential expression of β-defensins by HCECs may be observed when the cells are in a hyperosmolar environment.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…17,18 Human β-defensin-1 (hBD-1) and hBD-3 are constitutively expressed by the corneal and conjunctival epithelia, 18-20 whereas the expression of hBD-2 is inducible by proinflammatory cytokines such as IL-1α, IL-1β, TNF-α, bacterial by-products such as lipopolysaccharide and heat-killed Pseudomonas aeruginosa, and injury. [19][20][21][22] We have also observed that hBD-2 is expressed by conjunctival epithelial cells from patients with moderate dry eye but not in cells from normal subjects. 20 Because it has been reported that proinflammatory cytokines are secreted in greater amounts by HCECs in hyperosmolar media, 10 we reasoned that a differential expression of β-defensins by HCECs may be observed when the cells are in a hyperosmolar environment.…”
mentioning
confidence: 59%
“…[19][20][21][22] We have also observed that hBD-2 is expressed by conjunctival epithelial cells from patients with moderate dry eye but not in cells from normal subjects. 20 Because it has been reported that proinflammatory cytokines are secreted in greater amounts by HCECs in hyperosmolar media, 10 we reasoned that a differential expression of β-defensins by HCECs may be observed when the cells are in a hyperosmolar environment. Such a response may underlie our observation of conjunctival hBD-2 expression in dry eye patients but not normal subjects.…”
mentioning
confidence: 59%
“…19,[68][69][70] Furthermore, infiltrating neutrophils and macrophages present in the cornea as a result of microbial challenge also play an important role in limiting bacterial invasion by the production of certain peptides including the cathelicidins. Findings from the present study showed that functional activities of cathelicidin are necessary for bacterial clearance and innate corneal immunity at the ocular surface.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the vessel growth observed in the KO mice could have been initiated by the higher number of infiltrating neutrophils and possibly macrophages, as these cells contain significant amounts of angiogenic mediators that can be released in response to cellular activation. [65][66][67] Notably, the ability of cytokines to induce other cytokines and pro-and/or antiangiogenic factors secondarily and function as chemotactic factors for inflammatory cells makes it difficult to sort out the final and critical mediators of angiogenesis, infiltration, and inflammation conclusively in vivo.In the cornea, epithelial cells are a source of various antimicrobial peptides (including CRAMP, data not shown), particularly after injury or in response to inflammatory 19,[68][69][70] Furthermore, infiltrating neutrophils and macrophages present in the cornea as a result of microbial challenge also play an important role in limiting bacterial invasion by the production of certain peptides including the cathelicidins. Findings from the present study showed that functional activities of cathelicidin are necessary for bacterial clearance and innate corneal immunity at the ocular surface.…”
mentioning
confidence: 99%
“…DES also leads to an increase the risk of secondary infections 1) . Research has demonstrated that inflammatory cytokines including interleukin-1 (IL-1), interleukin-6 (IL-6), interleukin-8 (IL-8), and tumor necrosis factor-alpha (TNF-) are highly expressed in tears of patients with multi-factorial DES [2][3][4][5][6][7] . Moreover, current research suggests that neurogenic inflammation induced by neuropeptides may be closely associated with both the initial immune response and chronic inflammation in the disease 8) .…”
Section: Introductionmentioning
confidence: 99%